Valuing the lived experience: a phenomenological study of skiing*. Issue 2 (1st February 2018) - Clark, Kerensa; Ferkins, Lesley; Smythe, Liz; Jogulu, Uma
Abstract: Hermeneutic phenomenology is a little used approach in sport settings yet is widely advocated in other disciplines (e.g. health research). This article contributes to the theoretical understanding and practical application of hermeneutic phenomenology in sport research. It considers and explores the lived experience of skiing through a phenomenological approach and in so doing exposes a deeper understanding into the meaning skiing may hold in the lifeworlds of those who ski. Such research highlights the growing use of interpretive paradigms to elucidate lived experience in sport research, contrasting measurement of experience with seeking to understand the experiences themselves. We assert that hermeneutic phenomenology has much to offer sport research where an understanding of how one's subjective encounter can reveal much about the shared knowings, meanings and experiences of participation in sport in our society.